Measurement and Analysis of PM10 and PM2.5 from Chimneys of Coal-fired Power Plants Using a Light Scattering Method - Dongho Shin; Younghun Kim; Kee-Jung Hong; Gunhee Lee; Inyong Park; Hak-Joon Kim; Yong-Jin Kim; Bangwoo Han; Jungho Hwang (Aerosol and Air Quality Research)
Abstract Aerial pollutants emitted from the stacks of coal-fired power plants are considered a major source of fine particulate matter released into the atmosphere. To manage fine and coarse particles in the stacks themselves, it is necessary to know the concentration of fine and coarse particles emitted in real time; the current system to do so is tedious. In this study, a system for measuring PM2.5 and PM10 emitted from the stacks of power plants in real-time was developed, and measurements were performed on six coal-fired power plants. Through these measurements, the mass concentration distribution, according to particle sizes, could be determined. All six stacks showed bimodal distribution, and the count median diameters of each mode were 0.5 µm and 1.1 µm. Additionally, data were compared using the gravimetric measurement method; it was found that the relative accuracies for the measured PM10 amounts were within 20% and that the values obtained using the measuring instrument proposed in this study were reliable. Three power plants were continuously measured for one month, and by comparing PM10 concentration according to the amount of power generated, it was confirmed that PM10 discharged from the stack increased as an exponential function, depending on the amount of power generated.